Answer:
We can place everything with v(x) on one side of the equality, everything with x on the other side. This is done on the step-by-step explanation, and shows that the new equation is separable.
Step-by-step explanation:
We have the following differential equation:
[tex]xy' = y(ln x - ln y)[/tex]
We are going to apply the following substitution:
[tex]y = xv(x)[/tex]
The derivative of y is the derivative of a product of two functions, so
[tex]y' = (x)'v(x) + x(v(x))'[/tex]
[tex]y' = v(x) + xv'(x)[/tex]
Replacing in the differential equation, we have
[tex]xy' = y(ln x - ln y)[/tex]
[tex]x(v(x) + xv'(x)) = xv(x)(ln x - ln xv(x))[/tex]
Simplifying by x:
[tex]v(x) + xv'(x) = v(x)(ln x - ln xv(x))[/tex]
[tex]xv'(x) = v(x)(ln x - ln xv(x)) - v(x)[/tex]
[tex]xv'(x) = v(x)((ln x - ln xv(x) - 1)[/tex]
Here, we have to apply the following ln property:
[tex]ln a - ln b = ln \frac{a}{b}[/tex]
So
[tex]xv'(x) = v(x)((ln \frac{x}{xv(x)} - 1)[/tex]
Simplifying by x,we have:
[tex]xv'(x) = v(x)((ln \frac{1}{v(x)} - 1)[/tex]
Now, we can apply the above ln property in the other way:
[tex]xv'(x) = v(x)(ln 1 - ln v(x) -1)[/tex]
But [tex]ln 1 = 0[/tex]
So:
[tex]xv'(x) = v(x)(- ln v(x) -1)[/tex]
We can place everything that has v on one side of the equality, everything that has x on the other side, so:
[tex]\frac{v'(x)}{v(x)(- ln v(x) -1)} = \frac{1}{x}[/tex]
This means that the equation is separable.